Neochlorogenic acid: an anti-HIV active compound identified by screening of Cortex Mori [Morus Alba L. (Moraceae)] - Jing Li; Lu Dou; Shuangfeng Chen; Honghao Zhou; Fangzheng Mou (Taylor & Francis Group, 2021)
Context Chinese herbs such as Cortex Mori [Morus alba L. (Moraceae)] may inhibit human immunodeficiency virus (HIV), but active compounds are unknown. Objective Screening of Cortex Mori and other herbs for anti-HIV active compounds. Materials and methods HIV-1 virus (multiplicity of infection: 20), and herbs (dissolved in dimethyl sulfoxide, working concentrations: 10, 1, and 0.1 mg/mL) such as Cortex Mori, etc., were added to 786-O cells (105 cell/well). Zidovudine was used as a positive control. Cell survival and viral inhibition rates were measured. The herb that was the closest inactivity to zidovudine was screened. Mass spectrometry identified the active compounds in herbs (mobile phase: 0.05% formic acid aqueous solution and acetonitrile, gradient elution, detection wavelength: 210 nm). The effect of the compounds on reverse transcriptase (RT) products were evaluated by real-time PCR. Gene enrichment was used to analyse underlying mechanisms. Results With a dose of 1 mg/mL of Cortex Mori, the cell survival rate (57.94%) and viral inhibition rate (74.95%) were closest to the effect of zidovudine (87.87%, 79.81%, respectively). Neochlorogenic acid, one of the active ingredients, was identified by mass spectrometry in Cortex Mori. PCR discovery total RT products of neochlorogenic acid group (mean relative gene expression: 6.01) significantly inhibited (control: 35.42, p < 0.0001). Enrichment analysis showed that neochlorogenic acid may act on haemopoietic cell kinase, epidermal growth factor receptor, sarcoma, etc., thus inhibiting HIV-1 infection. Conclusions For people of low socioeconomic status affected by HIV, Chinese medicine (such as Cortex Mori) has many advantages: it is inexpensive and does not easily produce resistance. Drugs based on active ingredients may be developed and could have important value.